An Investigation of the Managerial Practices and Attitudes toward Organisational Culture Management in Western Australia - Wong, Harry; Alexander, Paul; Venable, John (ANZAM Org, 2012)
Various studies have confirmed the widespread influence of Organisational Culture (OC) on success and failure in organisations. Researchers have confirmed the relationship between OC and specific outcomes like organisational performance and productivity, technology adoption, and organisational growth. Appropriately managing OC is therefore seen as a way to facilitate organisational change and improvement. Despite the importance of OC in supporting the overall success of organisations, relatively few studies have been undertaken on OC Management (OCM) in Australia. In this exploratory investigation the practices and attitudes of managers toward OCM in the context of Western Australia (WA) are surveyed to determine the importance of OCM, which aspects are most important to managers, and the practices in managing OC.